2019
DOI: 10.1016/j.parkreldis.2019.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discrimination threshold and blink reflex recovery cycle in cervical dystonia – two sides of the same coin?

Abstract: Number of references: 13 (> 12) Number of figures: 2 (<=2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Beside dystonia affecting the head, neck and shoulder muscles as well as action induced tremors, there are numerous non-motor deficits in CD (Kuyper et al 2011 ). These include sensory abnormalities, such as pain (Tinazzi et al 2019 ), sensory tricks (Sarasso et al 2020 ), altered temporal and spatial discrimination (Junker et al 2019 ; Conte et al 2019 ) and impaired temperature detection threshold (Paracka et al 2017 ). Furthermore, there are mild neuropsychological deficits (such as deficits of memory, verbal fluency and executive functioning) as well as psychiatric alterations (such as depression and anxiety) (Kuyper et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beside dystonia affecting the head, neck and shoulder muscles as well as action induced tremors, there are numerous non-motor deficits in CD (Kuyper et al 2011 ). These include sensory abnormalities, such as pain (Tinazzi et al 2019 ), sensory tricks (Sarasso et al 2020 ), altered temporal and spatial discrimination (Junker et al 2019 ; Conte et al 2019 ) and impaired temperature detection threshold (Paracka et al 2017 ). Furthermore, there are mild neuropsychological deficits (such as deficits of memory, verbal fluency and executive functioning) as well as psychiatric alterations (such as depression and anxiety) (Kuyper et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical judgement should guide the decision on diagnostic testing, based on neurological assessment. Neurophysiological studies on iCD have shown increased muscle-muscle coherence, 66 abnormal temporal discrimination threshold, and blink reflex recovery curve, 67 but their value as endophenotypic markers has not been ascertained. Attempts to identify iCD subtypes based on neurophysiology have not been successful to date.…”
Section: Resultsmentioning
confidence: 99%
“…The first control group of healthy professional musicians was recruited from orchestras, music schools and universities in Berlin. Data of 12 individuals from the second non-musician control group have been reported previously 28 . Additional eight non-musicians were recruited from hospital staff of the Charité.…”
Section: Methodsmentioning
confidence: 99%